Psychological Reactions among Staffs of a Tertiary Eye Hospital in Eastern Nepal during COVID-19 Pandemic - Gautam Joshi, Rinku; Joshi, Purushottam; Shrestha, Pranav; Basnet, Prabha Subedi; Mahat, Pawan (Nepalese Journal of Ophthalmology, 2021)
Introduction: Eye examination and different procedures performed in close contact with eye and face, put medical and non medical staff of an eye hospital at higher risk for COVID-19. This causes increased psychological burden. The objective of this study was to find out depression, anxiety, stress and insomnia among Mechi Eye Hospital staff.Materials and methods: A web based cross-sectional study among Mechi Eye Hospital staff was done from 1st to 20th July 2020. Insomnia Severity Scale and DASS-21 were used.Results: Out of 220, 190 (86.6%) participated, 63.2% were female and 61.05% were medical staff with an overall mean age of 31.1±8.4 years. Overall prevalence of anxiety, depression, insomnia and stress were 20.5%, 18.9%, 16.3% and 12.6% respectively and  those were common in female with 63.9% (p value